Penilaian Keberkesanan Malaysian Highway Capacity Manual Dalam Rekabentuk Persimpangan Berlampu Isyarat Di Malaysia - Toh, Bin Tee (Universiti Sains Malaysia, 2006)
Civil Engineer should be competent in designing signalized intersection. It is essential for engineer to understand the concept and procedure of designing the signalized intersection by referring to the design manual. A new manual, which is more relevant to the traffic condition of Malaysia, Malaysian Highway Capacity Manual was completed. In this study, the determination of the effectiveness of the Malaysian Highway Capacity Manual is carried out by comparing the manual with the HCM 2000 and the Arahan Teknik (Jalan) 13/87. The results of the study have shown that the control delay estimated using the MHCM is significantly similar to the Malaysian Road condition as compared to the control delay estimated using other manuals.